The estimation of young water fraction based on isotopic signals: challenges and recommendations - Xia, Chengcheng; Zuecco, Giulia; Chen, Ke; Liu, Li; Zhang, Zhiliang; Luo, Jian (Frontiers in Ecology and Evolution, 2023)
Young water fraction (Fyw) is defined as the fraction of water in a stream with a transit time of less than 2-3 months. Fyw is a metric used to quantify the proportion of precipitation input converted into the runoff in the form of fast flow, which provides new insights for characterizing the mechanisms of water storage and release, understanding the time-scale of ecohydrological processes and indicating water-related risks. However, the Fyw has been advanced for a relatively short time, and the research on its applicability conditions and main drivers is still ongoing. Studies estimating Fyw are still very few and this index has not been reported in many landscapes and climate backgrounds, limiting its further application in hydrological studies. On the basis of summarizing the progresses of Fyw in previous studies, this paper provides a preliminary analysis of the potential uncertainties in Fyw estimation, which can be due to temporal trends in the isotopic composition of precipitation, uneven sampling interval of stream water, and complex hydrological systems. Finally, this paper provides some recommendations for the optimization of the sampling design and the methods used for Fyw estimation.